A review of risk management process in construction projects of developing countries - S. I., Doh; R. A., Bahamid (IOP Publishing, 2017)
In the construction industry, risk management concept is a less popular technique. There are three main stages in the systematic approach to risk management in construction industry. These stages include: a) risk response; b) risk analysis and evaluation; and c) risk identification. The high risk related to construction business affects each of its participants; while operational analysis and management of construction related risks remain an enormous task to practitioners of the industry. This paper tends towards reviewing the existing literature on construction project risk managements in developing countries specifically on risk management process. The literature lacks ample risk management process approach capable of capturing risk impact on diverse project objectives. This literature review aims at discovering the frequently used techniques in risk identification and analysis. It also attempts to identify response to clarifying the different classifications of risk sources in the existing literature of developing countries, and to identify the future research directions on project risks in the area of construction in developing countries.